2015
DOI: 10.1002/jcc.24207
|View full text |Cite
|
Sign up to set email alerts
|

Re‐evaluation of the bond length–bond strength rule: The stronger bond is not always the shorter bond

Abstract: A set of 42 molecules with N-F, O-F, N-Cl, P-F, and As-F bonds has been investigated in the search for potential bond anomalies, which lead to reverse bond length-bond strength (BLBS) relationships. The intrinsic strength of each bond investigated has been determined by the local stretching force constant obtained at the CCSD(T)/aug-cc-pVTZ level of theory. N-F or O-F bond anomalies were found for fluoro amine radicals, fluoro amines, and fluoro oxides, respectively. A rationale for the deviation from the norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
74
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 97 publications
(169 reference statements)
2
74
0
Order By: Relevance
“…It is interesting that all cases in which such bond anomalies were observed involve bonds between electronegative elements that carry lone‐pair orbitals. Very recently, Kraka and co‐workers reported a systematic investigation on the bond length/force constant correlation of 42 molecules with particular emphasis on species that exhibit a reverse relationship between bond lengths and force constants . The deviation from Badger's role was explained in terms of electron withdrawal together with strong orbital contraction and through‐space lone‐pair repulsion between electronegative atoms.…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting that all cases in which such bond anomalies were observed involve bonds between electronegative elements that carry lone‐pair orbitals. Very recently, Kraka and co‐workers reported a systematic investigation on the bond length/force constant correlation of 42 molecules with particular emphasis on species that exhibit a reverse relationship between bond lengths and force constants . The deviation from Badger's role was explained in terms of electron withdrawal together with strong orbital contraction and through‐space lone‐pair repulsion between electronegative atoms.…”
Section: Resultsmentioning
confidence: 99%
“…The associated local stretching force constants k a are used to probe the intrinsic strength of chemical bonds . It has been shown that the local stretching force constant k a is a superior bond strength measure compared to the often used bond dissociation energies (BDE) and bond dissociation enthalpies (BDH) as they contain cumulative effects of geometry relaxation, multiple bonding interactions, and also electronic density reorganizations of the dissociated fragments . Local stretching force constants k a have been successfully used to determine the intrinsic bond strength of covalent bonds such as: CC bonds, NN bonds, NF bonds, CO bonds, and CX (X=F, Cl, Br, I) bonds, and weak chemical interactions such as: hydrogen bonding, halogen bonding, pnicogen bonding, chalcogen bonding, tetrel bonding, and recently BH···π interactions …”
Section: Introductionmentioning
confidence: 99%
“…[25,[73][74][75] It has been shown that the local stretching force constant k a is a superior bond strength measure compared to the often used bond dissociation energies (BDE) and bond dissociation enthalpies (BDH) as they contain cumulative effects of geometry relaxation, multiple bonding interactions, and also electronic density reorganizations of the dissociated fragments. [73,76,77] Local stretching force constants k a have been successfully used to determine the intrinsic bond strength of covalent bonds such as: CC bonds, [74,75,78,79] NN bonds, [80] NF bonds, [81] CO bonds, [82] and CX (X = F, Cl, Br, I) bonds, [83][84][85][86] and weak chemical interactions such as: hydrogen bonding, [87][88][89][90] halogen bonding, [91][92][93] pnicogen bonding, [94][95][96] chalcogen bonding, [73,77] tetrel bonding, [97] and recently BH � � � p interactions. [16,17] The main objectives of this paper are: (i) to evaluate the nature of the BÀ B, BÀ H b , and BÀ H t bonds; (ii) to evaluate why intermediate species may or may not facilitate the reversibility reactions in the perspective of thermodynamics and intrinsic bond strength; (iii) to provide a new tool to characterize new (potential) intermediates and their role for the reversibility of the hydrogenation/dehydrogenation reactions; and (iv) to give guidelines whether intermediates may be stable enough to be isolated.…”
Section: Introductionmentioning
confidence: 99%
“…At the core of the problem lies the non‐measurability of bond energies in polyatomic molecules, although discussions already flourish even in diatomics . So important is the concept to Chemistry, and so deeply rooted it is in the chemist's mind that, even today, the role of empirical bond‐length bond‐strength correlations, like Badger's rule, are the subject of renewed discussions …”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14] So important is the concept to Chemistry,a nd so deeply rooted it is in the chemist's mind that, even today, the role of empirical bondlength bond-strength correlations,l ike Badger'sr ule, [15,16] are the subject of renewed discussions. [17,18] Te xtbooks teach that the bond dissociation energy (BDE, D e ), the energy required to split ag round-statem olecule AÀBi nto its fragments in their respective ground states,m easures bond strength.H owever,B DEs, whichc an be determined either experimentally or computationally, [4] mayo nly be considered descriptorsofbond energies (BEs) in diatomics.…”
Section: Introductionmentioning
confidence: 99%